الفساد ومدلولاته في ضوء القرآن الكريم والسُّـنَّة النبوية - م. طارق طاهر عبد الله (Prosiding Konferensi Nasional Bahasa Arab, 2021)
The research was interested in studying the implications of corruption in the light of the Holy Qur’an and the Prophetic Sunnah, as this word was mentioned many times in the Qur’an and Sunnah. In the research, the researcher shows the most prominent meanings of corruption and its forms, using the books of interpretation and hadith and their meanings.Keywords: corruption, implications, phenomenon